Testing drought tolerance of wheat by a complex stress diagnostic system installed in greenhouse - Majer, Petra (Acta Biologica Szegediensis, 2008)
Drought is one of the most important abiotic stress factors and depending on the season it can seriously limit wheat production. Breeding for drought tolerance is becoming a more and more important challenge in case of crop plants, notably in wheat. The breeding process includes the characterization of the basic breeding materials in aspect of performance under well-watered and drought stressed conditions. In our experiments we set up a complex stress diagnostic system in the greenhouse of the Cereal Research Non-profit Company where we could analyze the responses of different winter and spring wheat cultivars to drought. Wheat plants were grown under ideal water regime (watering to 60% of the 100% soil water capacity) and under drought stress conditions (watering to 20% of the 100% soil water capacity). The effect of water withholding on plant growing was tracked by a digital imaging system on the basis of number of plant pixels. After harvesting, plant heights, spike lengths, grain numbers and total grain weights were measured and values of well-watered and stressed plants were compared. Here the measured parameters of two drought tolerant (Sardari, GK 11-05) and two drought sensitive (Kärtner Früh, Jing 411) wheat genotypes are presented to prove the competence of our system in characterizing drought tolerance of wheat plants.